The Effectiveness of Booklet Media on Knowledge About Anemia Among Adolescent Girls at Junior High School in Bandar Lampung - Hardjasasmita, Aisyah Amalia Putri; Suja, Monica Dara Delia; Mugiati, Mugiati; Septiani, Ranny (NSMRJ: Nusantara Scientific Medical Research Journal, 2025)
Anemia is a common health problem among adolescent girls, often caused by a lack of knowledge regarding its causes, symptoms, and prevention methods. Therefore, appropriate educational efforts are needed to improve awareness and understanding of anemia among teenagers. Booklets are considered an effective and accessible educational medium, particularly for adolescent groups. This study aimed to determine the effectiveness of booklet media in increasing knowledge about anemia among female students at SMP Negeri 14 Bandar Lampung. This study used a quantitative approach with a one-group pretest–posttest design. A total of 230 students were selected using Slovin’s formula. Data were collected using a 25-item questionnaire administered before and after the booklet intervention. Because the data were not normally distributed, analysis was conducted using the Wilcoxon Signed Rank Test. The mean pretest score was 42.52 and increased significantly to 98.99 in the posttest. The Wilcoxon test showed a significance value of p < 0.05 (p = 0.000), indicating a statistically significant difference in knowledge before and after the booklet intervention. In conclusion, booklet media is proven to be effective in improving adolescent girls’ knowledge about anemia. It serves as an easily understood educational tool and can be utilized to support school-based health education programs.